Remote Sensing and GIS Techniques in Monitoring Land Use Land Cover Change - Sameer, Mohammed Kareem; Hamid, Adnan Muttashar (International Journal of Sustainable Construction Engineering and Technology, 2023)
This examination by utilizing GIS and Remote Sensing procedures to planning highlights of Al-Kut city, Iraq from 2004 to 2014, in order to classify developments that has occurred between these periods. The using of satellite image (Quick bird satellite) with depending on remote detecting and GIS to identify Land Use/Land Cover change which is defined as the amount of the distinct information and current change data that can incite continuously touchable bits of information into basic strategies, including land spread and land use changes. The process of defining the Changes related to LULC properties called change detection and it’s referenced to Geo-registered high resolution. It is useful in many applications such as identification of land use changes, the amount of deforestation, urban extension, and other cumulative changes through spatial and historical analysis techniques. The dependable method briefly by data acquisition (satellite image with resolution 0.60 m) and geo-referenced with GCPs to produce a thematic map of feature classified and making the statistical analyzing.ARC map software help us to make this easy by depending on entering two types of data, first one is satellite image and second one is ground control points. This study shows a development in built-up land and expansion from 2004 to 2014, however in the city, land decreasing, which is due to the development and growth in it. Finally, the result shows the decreasing in waterbodies and waste land area with noticed increasing of using land. These progressions are mainly happening with uncontrolled urban growth.